2016
DOI: 10.1063/1.4942555
|View full text |Cite
|
Sign up to set email alerts
|

Homoepitaxial graphene tunnel barriers for spin transport

Abstract: Tunnel barriers are key elements for both charge-and spin-based electronics, offering devices with reduced power consumption and new paradigms for information processing. Such devices require mating dissimilar materials, raising issues of heteroepitaxy, interface stability, and electronic states that severely complicate fabrication and compromise performance. Graphene is the perfect tunnel barrier. It is an insulator out-of-plane, possesses a defect-free, linear habit, and is impervious to interdiffusion. None… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…From the nonlocal spin valve measurements, they achieved spin injection efficiencies up to 45% and 17% at low temperatures for fluori-nated and hydrogenated graphene-based tunnel barriers, respectively. However calculated spin relaxation times in these devices are less than 0.2 ns and the created spin accumulation is very small or even absent at room temperature (Friedman et al, 2016). Recently, Gurram et al (2017) have observed bias-induced enhanced spin injection and detection efficiencies up to 100% in tunnel junctions with bilayer hBN barriers.…”
Section: B Advances In Spin Injection Contactsmentioning
confidence: 99%
“…From the nonlocal spin valve measurements, they achieved spin injection efficiencies up to 45% and 17% at low temperatures for fluori-nated and hydrogenated graphene-based tunnel barriers, respectively. However calculated spin relaxation times in these devices are less than 0.2 ns and the created spin accumulation is very small or even absent at room temperature (Friedman et al, 2016). Recently, Gurram et al (2017) have observed bias-induced enhanced spin injection and detection efficiencies up to 100% in tunnel junctions with bilayer hBN barriers.…”
Section: B Advances In Spin Injection Contactsmentioning
confidence: 99%
“…For a defect-free barrier, spin injection of 26-30% and a large spin signal of 130 Ω have been reported. [52] The use of 2D materials such as hexagonal boron nitride (hBN) [74][75][76][77] and fluorinated graphene [78] as tunnel barriers exhibit high spin injection efficiency. The advantage of 2D materials is the absence of defects such as pinholes and an atomically flat surface.…”
Section: Spin Injection and Scatteringmentioning
confidence: 99%
“…For hBN, experimental works [3,4,9,12,[32][33][34] suggest a value of the decay constant c(0) ≈ 5nm −1 . In the case of graphene, studies of its role as a barrier in magnetic tunnel junctions [35][36][37] and between metal contacts [38,39] showed that it behaves as a strong out-of-plane insulator. In fact, in experiments conducted in the absence of a magnetic field and in the presence of a field parallel to the graphene layers, the measured tunnelling current has been well described by assuming that all tunnelling from the further BLG layer is suppressed [10,12].…”
Section: Device Description and Tunnelling Matrix Elementmentioning
confidence: 99%